2008
DOI: 10.1016/j.ygcen.2008.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiodic induced changes in reproductive state of border canaries (Serinus canaria) are associated with marked variation in hypothalamic gonadotropin-releasing hormone immunoreactivity and the volume of song control regions

Abstract: In temperate zone songbirds, such as canaries (Serinus canaria), seasonal variation in gonadal activity and behavior are associated with marked brain changes. These include gonadotropinreleasing hormone (GnRH) expression and the volume of brain areas controlling song production. Questions have been raised about the consistency of seasonal brain changes in canaries. Laboratory studies of the American singer strain raised doubts as to whether this strain exhibits a robust photoperiodic response along with change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 43 publications
4
25
0
Order By: Relevance
“…1). In addition the measured volumes of HVC and RA were well within the range of previously published findings in canaries (Gahr, 1990;Hurley et al, 2008;Bottjer, 1993, 1995;Catchpole, 2004, 2007).…”
Section: Data Presentation and Validationsupporting
confidence: 88%
“…1). In addition the measured volumes of HVC and RA were well within the range of previously published findings in canaries (Gahr, 1990;Hurley et al, 2008;Bottjer, 1993, 1995;Catchpole, 2004, 2007).…”
Section: Data Presentation and Validationsupporting
confidence: 88%
“…Our studies of captive male and female canaries have shown that males exhibit a clear increase in T circulating concentrations in response to long days that declines when the birds go photoreractory while female serum T concentrations never exceed concentrations measured in photosensitive males held on short days (Hurley et al, 2008). Pesch and Güttinger (1985) studied spontaneous song in socially isolated adult female canaries.…”
Section: Discussionmentioning
confidence: 80%
“…Treatment of captive white-crowned sparrows held under long day conditions with exogenous T that increased plasma concentrations to 4-10 ng/ml did result in an increase in HVC volume within one week (Tramontin et al, 2000). However, we maintained our birds on short days and birds with the largest implants had T concentrations of about 2 ng/ml, which reflects the highest concentrations we had measured in male canaries previously (Hurley et al, 2008). Field studies of white-crowned sparrows have now demonstrated that T concentrations below 2ng/ml are sufficient to induce growth of the song system in these birds albeit with a time course longer than 1 week (Tramontin et al, 2001).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…For this reason they are referred to as being “seasonal opportunistic breeders”[100]. There are interesting differences in two canary strains with the American singer strain maintaining high levels of GnRH1 in the presence of prolonged exposure to long days [16] and the Border strain exhibiting gonadal involution, along with a marked decrease in GnRH1 expression [87]. The American singer strain seems to have lost over the course of domestication the native responsiveness to photoperiod that is maintained in the Border strain.…”
Section: Co-evolution Of Neuropeptide Plasticity and Seasonal Reprmentioning
confidence: 99%